Sphingomonas from petroleum-contaminated soils in Shenfu, China and their PAHs degradation abilities - Zhou,Lisha (2016)
Abstract Members of the Sphingomonas genus are often isolated from petroleum-contaminated soils due to their unique abilities to degrade polycyclic aromatic hydrocarbons (PAHs), which are important for in situ bioremediation. In this study, a combined phenotypic and genotypic approach using streptomycin-containing medium and Sphingomonas -specific PCR was developed to isolate and identify culturable Sphingomonas strains present in petroleum-contaminated soils in the Shenfu wastewater irrigation zone. Of the 15 soil samples examined, 12 soils yielded yellow streptomycin-resistant colonies. The largest number of yellow colony-forming units (CFUs) could reach 105 CFUs g-1 soil. The number of yellow CFUs had a significant positive correlation (p < 0.05) with the ratio of PAHs to total petroleum hydrocarbons (TPH), indicating that Sphingomonas may play a key role in degrading the PAH fraction of the petroleum contaminants at this site. Sixty yellow colonies were selected randomly and analyzed by colony PCR using Sphingomonas -specific primers, out of which 48 isolates had PCR-positive signals. The 48 positive amplicons generated 8 distinct restriction fragment length polymorphism (RFLP) patterns, and 7 out of 8 phylotypes were identified as Sphingomonas by 16S rRNA gene sequencing of the representative strains. Within these 7 Sphingomonas strains, 6 strains were capable of using fluorene as the sole carbon source, while 2 strains were phenanthrene-degrading Sphingomonas. To the best of our knowledge, this is the first report to evaluate the relationship between PAHs contamination levels and culturable Sphingomonas in environmental samples.